2021
DOI: 10.2217/nnm-2020-0481
|View full text |Cite
|
Sign up to set email alerts
|

Cleavable Poly(Ethylene Glycol) Branched Chain-Modified Antheraea Pernyi Silk Fibroin as A Gene Delivery Carrier

Abstract: Aim: To obtain a gene carrier that can effectively deliver loaded therapeutic genes to tumor cells, avoid toxic effects on normal cells and reduce nonspecific adsorption of plasma proteins. Methods: The conjugate of poly(ethylene glycol) (PEG) and MMP2SSP (PEG-MMP2SSP) was covalently coupled to cationized Antheraea pernyi silk fibroin (CASF) through disulfide bond exchange reaction to obtain a PEG-MMP2SSP-modified CASF (CASFMP). Results: The PEG chains were effectively cleaved from the CASFMP by MMP2. CASFMP/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…32 Examples of this technique include a micelle incorporating zwitterionic carbomethyl chitosan to assist with endosomal escape 83 and a micelle which reveals a cationic surface after PEG is cleaved in the tumour microenvironment following enzymatic cleavaged. 84 Alternatively, effective uptake can be achieved whilst keeping a neutral surface charge by incorporating ligands which target internalising extracellular receptors. 85…”
Section: Modifying Nanomedicines For the Body: A Challenge To Outwit ...mentioning
confidence: 99%
“…32 Examples of this technique include a micelle incorporating zwitterionic carbomethyl chitosan to assist with endosomal escape 83 and a micelle which reveals a cationic surface after PEG is cleaved in the tumour microenvironment following enzymatic cleavaged. 84 Alternatively, effective uptake can be achieved whilst keeping a neutral surface charge by incorporating ligands which target internalising extracellular receptors. 85…”
Section: Modifying Nanomedicines For the Body: A Challenge To Outwit ...mentioning
confidence: 99%
“…Recent studies have found that some of these fibers expand the design space for silk-based materials by having more reactive residues and different mechanical properties. Recently, silk fibroin from Antheraea assamensis (Baruah et al, 2020;Asapur et al, 2022), Antheraea pernyi (Liu et al, 2021), and sericin from Antheraea mylitta (Nayak et al, 2021) have all been used in the development of nanoparticle DDS (Table 1). Asapur et al (2022) characterized the secondary structure of nanoparticles synthesized from Antheraea assamensis fibroin by desolvation and radiolysis methods.…”
Section: Non-bombyx Mori Native Silk Fibersmentioning
confidence: 99%
“…Baruah et al (2020) evaluated the release of doxorubicin from Antheraea assamensis fibroin particles made by desolvation and found efficient drug loading, and that the DDS increased the effectiveness relative to free doxorubicin of the cytotoxic effect on MDA-MB-231 cancer cells. Liu et al (2021) took advantage of the abundant reactive sites present in silk fibroin from Antheraea pernyi in the creation of their stimuli responsive DDS. They prepared particles from cationized Antheraea pernyi fibroin for gene delivery to cancer cells by desolvation in DMSO.…”
Section: Non-bombyx Mori Native Silk Fibersmentioning
confidence: 99%
See 1 more Smart Citation